Effect of patch dimension and fiber orientation on non-linear buckling of hybrid composites - Erdem, Serkan; Gur, Mustafa; Kaman, Mete Onur (Walter de Gruyter Gmbh, 2021)
In this study, first circular hole layered hybrid composite plates were repaired by wet patch method, and then buckling behavior was investigated experimentally and numerically. In the experimental study, composite plates were produced by vacuum infusion method using hybrid fabrics made of carbon and aramid. Circular holes were drilled in the produced plates and then these holes were repaired with the same material. In the wet patch repair method, wet hybrid fabrics impregnated with epoxy resin were placed around the hole and then this area was subjected to pressure and temperature by vacuum infusion method. In experimental tests, pressure force was applied to the fixed sides and force-displacement graphs were obtained. In a numerical study, non-linear buckling analysis was performed by creating numerical models of plates and patches using the finite element method. As a result, experimental and numerical load-displacement graphs were obtained in accordance with pre- and post-buckling. Thanks to the repair in accordance with practical applications, no interface debonding damage occurred in ideal samples. Increasing the patch length from 30 mm to 40 mm increased the maximum damage load by 6 %, while increasing the patch length to 50 mm increased damage load by 12 %. Increasing the patch thickness from 0.65 mm to 1.1 mm increased the load by 67 %, while increasing it to 2.16 mm increased the load to 247 %. Fiber orientation was found to be a more influencing factor in critical buckling and damage load than the ply sequence.
Keywords: Wet patch; post-buckling; repair; hybrid composites; non-linear analysis